Reading the body: the rhetoric of sex, identity and discipline in girls' education - Charania, Munira Moon (International Journal of Qualitative Studies in Education, 2010)
This essay focuses on key contemporary rhetoric, discourse, and practice directly speaking to or about adolescent girls. Using ethnographic work done at a southeastern all-girls' school, I examine the adolescent female body as a palimpsest, a rich and dense text subjected to and shaped by public rhetoric and pedagogical practice. I suggest that the identity of girl is made and remade by public rhetoric and pedagogic practice, always with various silences and elisions, always with shapes and disfigurements tolerated, so that the very texture of this identity, the adolescent female body, becomes a palimpsestic landscape, on which the original 'girl' is sought and modern versions are interpreted. I consider how public discourses on girls and girls' bodies are significant in the production of girls' identities, practices surrounding the empowerment and education of girls, and the very debates that centralize the adolescent female body as one in need of protection and surveillance.
Keywords: corps; cours; discipline; ethnographie; lit4700; premier cycle; ressource en ligne; sciences humaines; sociologie; thématiques